ACHIEVING THE BEST RESULTS AT THE GAMES OF THE OLYMPIAD BY ELITE JUDOKAS - Timofeev, V.D.; Makarov, V.V.; Brainin, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a comparative analysis of the achievement of the best results by judo athletes of the leading national teams at the Olympiad Games and the main competitions in the training cycle that preceded these Games, as well as to identify the information content of other indicators of the realization of the potential of national judo teams. Methods and structure of the study. In the course of the desk analysis, professional biographies of 121 judoka athletes were studied: 63 men and 58 women, who represented the four leading national teams of Japan, Russia, Georgia and France at the 2012, 2016 and 2020 Games. The results of the performances of athletes and teams at the Games of the Olympiad were compared with the results at the main starts of the seasons in the previous training cycles: world championships, previous Games of the Olympiad, world series tournaments. Results and conclusions. The most conservative characteristics of both men’s and women’s national teams that won the first team place in the Olympic tournaments are the presence of winners of the World Series tournaments (all participants), winners of the World Championships or the previous Olympiad (6-7 Olympians), world champions or Olympic champions of the previous Olympiad (2-6 Olympians). Along with this, the range of fluctuations in indicators characterizing the realization of the potential of athletes in the world’s leading judo teams is assessed as high. The foregoing indicates that coaching staffs are looking for programs that allow athletes to reach their full potential at the main start of the four years.